CLUBUL DE LECTURĂ – O MODALITATE EFICIENTĂ ÎN PROMOVAREA LECTURII - JUC, şef oficiu copii, Filiala „Târgovişte”, Liliana (BIBLIOPOLIS, 2020)
This article is an analysis of the efficient way to valorise book and reading. The Reading clubs: The little Europeans (Micii Europeni), The Curious (Curioşii), It’s good to know (E bine să știm!) ensure the realization of our objectives: satisfaction of users needs, presentations of reference collection, encouraging of reading, efficient holding of a Program Summer reading. The Reading club are multiple advantages: monitoring of the processus of text perception; analysis of child perception of reading; combination of various type of reading (informative, exploratory, literary, game and group reading); combination of various type of activities (discussion/debate, cognitive games, contests); creation of an agreable space for socialisation and creation of book’s dependence. The Reading Club is the most appropiate way to increase the reading appetence and the user loyalty.